PUBLIC SERVICE INNOVATION IN THE SMART GOVERNANCE ERA: STRATEGIES TO INCREASE TRANSPARENCY AND ACCOUNTABILITY - Iskandar, Ade (CosmoGov: Jurnal Ilmu Pemerintahan, 2025)
The transformation of public services in the era of smart governance increasingly relies on the use of digital technology to improve transparency and accountability. Digitalization of administration allows for the simplification of bureaucratic procedures, accelerates public access to information, and strengthens interaction between government and citizens. However, the implementation of this innovation faces challenges in terms of regulation, infrastructure readiness, and community involvement that are still diverse. This study aims to analyze the government's strategy for realizing technology-based public service innovations to improve government transparency and accountability. The method used in this study is a qualitative approach by collecting data from various relevant sources, including previous research and policy studies. The data obtained are then analyzed systematically to identify patterns, findings, and challenges faced in the implementation of smart governance. The results of the study show that the digitalization of public administration and technology-based accountability mechanisms can improve the effectiveness of governance. In addition, community involvement through online platforms and social media plays an important role in strengthening the transparency of public policies. Therefore, the success of public service innovation requires adaptive policy support, increased human resource capacity, and collaboration between the government, private sector, and academics.gb777